Market Access. Nuovi paradigmi manageriali e strumenti operativi per le imprese del Life Science (perché niente è più come prima) - Galliverti, Giuseppe (Ahead, 2023)
If the NHS and its healthcare companies have only recently become aware of being faced with a "new normality", and, therefore, of having to "shed their skin" to face the challenges connected to it, a new normality for Life Science companies, perhaps best described as a perfect storm, it has become a reality at least since the early years of the new century. The world in which access to the market, the introduction of innovation, and consolidation of sales were built around the supervision of regulatory processes and the share of voice towards the prescribers have become much more complex. A context that many define as VUCA (volatile, uncertain, complex, ambiguous). In this book, therefore, both the reasons that prompted Life Science companies to rethink their strategy by dedicating increasing attention to the political and institutional decision-makers of the Regions and the management of healthcare companies, and the internal organization to support and strengthen their "market access" capabilities. Through the different perspectives - academic, consultancy, managerial - of the three authors, the logic that has guided the "change of skin" of Life Science companies is explored, as the functional tools for market access, the different declinations that this activity has had in the sector, future scenarios and further evolutionary prospects, the connection with the other company functions - sales, marketing, medical management, institutional affairs, administration - and many technical aspects which are the heart of the skills and toolbox required of those who want to successfully develop a career right in the field of market access.